Factorial Analysis of Mass Media Influence on Academic Sports Development - Noshin Benar; Mina Emami; Ozra Eftekhari; Far Nastaran Yeganeh; Mohammadi Ali Mohammad Khan (Physical Education of Students, 2016)
Purpose: Main objective of this research was factorial analysis of mass media influence on academic sports development. Material: Methodology of the research was descriptive- correlation. Population of the research was composed of all referees, coaches and athletes participating in students' sports Olympiad of Iran Payam e Noor Universities in year 2014. Statistical sample of research was chosen randomly and consisted of 176 persons. Data gathering tool was a researcher made questionnaire; its superficial and content validity was approved by academic professors and media experts; also the stability of research tool was reported to be at an acceptable level. SPSS 23 software was used to analyze research data and also AMOS 24 software was used to analyze structure validity. Results: Findings showed there is a significant difference between current situation and desirable situation in all research dimensions. Also, factorial analysis of all research variables showed improvement of coaches' technical performance (0.86), improvement of referees' technical performance (0.85), and promotion of academic sport managers' awareness (0.83) respectively are mostly influenced by mass media. Conclusion: It should be kept in mind that academic sports development is one of the factors of the entire country sports development. Hence, it is crucial to attend to different dimensions of student sport's aspects such as human, financial, planning and etc., especially in championship area to be able to further macro objectives of country's sports development. Considering current conditions, mass media should have a new perspective on academic sports in order to be able to attend to their responsibilities to further the excellence of country's sports.